Anti-inflammatory Activity of Pyrazole Analogues Deduced from Bioactive Piperine: Synthesis, In silico, and In vitro Evaluation - Mathew, Lilbet; sankaranarayanan, Murugesan; Kaliappan, Ilango (Current Enzyme Inhibition, 2023)
Background: Around ten novel pyrazoline and pyrazolidine derivatives were designed and synthesized by the condensation of piperine, hydrazine hydrate, phenylhydrazine, aromatic carboxylic acid, and ethanol. Methods: The synthesized compounds (2, 3, 4a-d, and 5a-d) were characterized by FTIR, 1HNMR, mass spectral, and elemental analysis. Pharmacokinetic, physicochemical, drug-likeness, and medicinal chemistry friendliness parameters were also predicted by in silico methods. Results: Furthermore, compounds were screened for in vitro anti-inflammatory activity by the HRBC membrane stabilization method using diclofenac sodium as the standard drug. The tested compounds showed moderate anti-inflammatory activity compared to the standard drug. The molecular docking studies of significantly active (4d) and least active compounds (5d) were also carried out in the active sites of an arachidonate-12-lipoxygenase target in order to study the putative binding pattern of the study compounds. Conclusion: According to the findings of this study, further lead identification as well as lead optimization techniques will be required in the near future in order to get potent analogues.
Keywords: FTIR